2014
DOI: 10.1016/j.surfcoat.2014.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of oxide scale formed on ferritic stainless steels in simulated reheating atmosphere

Abstract: The aim of this study is to optimise the stainless steel oxidation behaviours during hot rolling. The high temperature oxidation behaviours of ferritic stainless steels B443NT and B445J1M were studied over the temperature range from 1000 to 1150 °C in a humid atmosphere containing 18% water vapour, as measured by a thermogravimetric analyser (TGA). The results indicate that breakaway oxidation occurs at 1090 °C for the B443NT steel, which is 60 °C lower than that for the B445J1M steel. The occurrence of iron o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 39 publications
2
39
0
5
Order By: Relevance
“…The sticking of bare metal to roll surfaces was strongly dependent on the high temperature tensile strength and the oxidation resistance of the stainless steel [1]. It is more difficult for oxide scale to be generated on the surface of stainless steels than that on the surface of carbon steels during high rolling temperature [2,3]. Sticking refers to a phenomenon occurring in hot rolling process in which fragments of a rolled material are detached and get stuck onto a work roll surface, deteriorating not only the surface quality of the product, but also the rolls, which will result in shorter intervals of roll replacement or grinding [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sticking of bare metal to roll surfaces was strongly dependent on the high temperature tensile strength and the oxidation resistance of the stainless steel [1]. It is more difficult for oxide scale to be generated on the surface of stainless steels than that on the surface of carbon steels during high rolling temperature [2,3]. Sticking refers to a phenomenon occurring in hot rolling process in which fragments of a rolled material are detached and get stuck onto a work roll surface, deteriorating not only the surface quality of the product, but also the rolls, which will result in shorter intervals of roll replacement or grinding [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…1 shows the surface of high speed steel (HSS) roll after the sticking occurs during rolling stainless steel grade B445J1M. The B445J1M steel has high oxidation resistance in the reheating environment [2]. The HSS rolls shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the oxide layer of B445J1M can be considered as a single layer of Cr 2 O 3 . Additionally, the separation can be clearly observed between the oxide scale and the substrate, which means the oxide scale of B445J1M poorly attached to the substrate [19]. Figure 4 shows the thickness of the B445J1M oxide scale vs time, from which can be obtained that its thickness reaches at approximately 4.6 m after oxidizing 2 hours.…”
Section: Characterization Of Oxide Scalementioning
confidence: 96%
“…Therefore, studying the influence of water vapor on Chromia-forming alloys oxidation at high temperature has great importance. Some works have been done to study the influence of water vapor on oxidation [1][2][3][4][5][6], and several mechanisms have been proposed to explain the influence of water vapor on oxidation, such as Fuji and Meussner [2] proposed a dissociation mechanism, and suggested that hydrogen appears to play an important role in the oxidation process as an oxygen carrier between the separated inner and outer scale layers. Shen Jianian [3] suggested that breakaway oxidation happened in the water vapor containing atmosphere is the result of formation of microcracks and microchannels during oxidation.…”
Section: Introductionmentioning
confidence: 99%